All‐In‐One Stainless‐Steel Mesh Oxide Composites Anode for Flexible Li‐Ion Battery. Issue 10 (5th August 2020) - Zhang, Baofeng; Xu, Youlong; Wang, Jie; Ma, Xiaoning; Lin, Jun; Wang, Chao; Xue, Xu
Abstract: For portable and wearable electronics, a flexible full battery can lead to tremendous development. However, certain issues with the anode still exist, such as complexity, low capacity, and poor stability. Herein, a flexible metal oxide (MOx) composite anode is synthesized in situ, which transfers a stainless‐steel mesh (SSM) to the SSM‐MOx‐900@PPy anode, with void‐array MOx nanoframeworks encapsulated within polypyrrole (PPy). The hierarchical structure offers a close connection and highly interpenetrated porous conductive network between PPy and MOx, which sufficiently constrains the volume changes and enhances the electronic conductivity. Besides, the binder‐free connection between the active material and current collector is effective for charge transport and robust structural stability during the electrochemical processes. The prepared SSM‐MOx@PPy anode exhibits low contact resistance, decreased charge transfer resistance, and enhanced Li + diffusion coefficient, resulting in an ultrahigh capacity of 1000 mAh g −1 at 0.1 C and outstanding cycling stability of 640.9 mAh g −1 with a retention rate of 99% after 100 cycles at 1 C. The high‐power full battery fabricated by the SSM‐MOx‐900@PPy and LiFePO4 can be bent and folded freely without obvious capacity attenuation (99.2% of the initial value after 100 bending cycles). These results may provide valuable guidance for designing advanced anodes. Abstract : Remarkable progress is made for the all‐in‐one flexible anode from stainless steel mesh. The hierarchical structure acquires the anode with lower contact resistance, lower discharge potential, higher energy density, and power density. The battery also exhibits impressive flexibility with 99.2% of initial value after 100 bending cycles, demonstrating great potential for flexible lead‐ion batteries (LIBs).